Role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in restaging and prognosis of recurrent melanoma after curative surgery - Dharmender Malik (World Journal of Nuclear Medicine, 2019)
Malignant melanoma is a highly aggressive tumor and surgical resection is the primary treatment. However, the chances of recurrence are quite high despite complete resection. The aim of study was to evaluate the 18F-fluorodeoxyglucose(18F-FDG) positron emission tomography–computed tomography (PET/CT) in detection of recurrent melanoma after curative surgery and its prognostic value. Fifty-four melanoma patients (32 women) with prior primary lesion resection were evaluated with 18F-FDG PET/CT for clinically suspicious recurrent disease. The diagnostic accuracy of 18F-FDG PET/CT (visual interpretation as well as semi-quantitative parameter) was determined on the basis of subsequent imaging and clinical follow-up. Melanoma-specific survival and risk of progression (hazard ratio [HR]) were assessed using Kaplan–Meier method and Cox regression analysis.18F-FDG PET/CT detected recurrent diseases in 36 (66%) patients including distant metastases in 13 patients and second synchronous malignancy in 2 patients. Overall, the sensitivity, specificity, positive predictive value, and negative predictive value of 18F-FDG PET/CT were 91.2%, 80.0%, 88.6%, and 84.2%, respectively, with area under the curve of 0.86 (95% confidence interval: 0.74–0.97; P < 0.05). Positive 18F-FDG PET/CT study was associated with a significantly shorter overall survival than negative study (30.8 ± 4.6 vs. 64.5 ± 6.9 months, P < 0.05). Apart from positive 18F-FDG PET/CT scan, maximum standardized uptake value (SUVmax) >2.7 and combination of both were independently associated with an increased risk of disease progression (HR = 7.72, 21.58, and 11.37, respectively; P < 0.05).18F-FDG PET/CT showed enhanced diagnostic performance in patients with suspicious recurrent malignant melanoma leading to appropriate management. FDG positivity along with SUVmax >2.7 provides important prognostic value in predicting the survival outcomes and assessing the risk of disease progression.